One-Pot Synthesis of Titanate Nanotubes Decorated with Anatase Nanoparticles Using a Microwave-Assisted Hydrothermal Reaction. (14th March 2019) - Gusmão, Suziete B. S.; Ghosh, Anupama; Marques, Thalles M. F.; Ferreira, Odair P.; Lobo, Anderson O.; Osajima, Josy A. O.; Luz-Lima, Cleanio; Sousa, Romulo R. M.; Matos, Jose M. E.; Viana, Bartolomeu C.
Abstract : A nanoheterostructure of titanate nanotubes decorated with anatase nanoparticles (TiNT@AnNP) was synthesized for the first time by a microwave-assisted hydrothermal one-pot reaction. Characterization by X-ray diffraction, Raman spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, high-resolution transmission electron microscopy, selected-area electron diffraction, and X-ray photoelectron spectroscopy showed highly crystalline and nanometer-sized TiNT@AnNP. The synthesized TiNT@AnNP degraded an anionic dye (Remazol blue) more efficiently under UV-visible light (380–780 nm) than a commercial anatase-TiO2 precursor. We correlated this increased efficiency of photodegradation to the large surface area and the efficient separation of photoinduced electron-hole pairs. Finally, we propose a mechanism to highlight the influence of a microwave-assisted hydrothermal synthesis in the production of TiNT@AnNP for environmental applications.